Effect on Academic Achievement and Misconceptions of Pre-service Teachers through Combining Different Teaching Methods in a Preschool Science Course - Nur Akcanca; Lale Cerrah Özsevgeç (Journal of Science Learning, 2020)
This study aimed to investigate the effects of different active teaching techniques on pre-school student teachers' concept learning and academic achievement. The study group consisted of 46 third year pre-school student teachers in a public university. Different active teaching methods were used during the single term Science Course, a compulsory course in the Preschool Programme. The treatment process took ten weeks in total (4 hours per week). The study had both qualitative and quantitative data. The quantitative data were collected using a three-tiered science concepts test, and qualitative data were collected through observation by the researcher. The alpha Cronbach values calculated for the test's reliability were 0.642 for Success-1 (S1) and 0.52 for Misconception-3 (MC3) scores. A dependent t-test was used to compare the pre and post-test scores of the pre-school student teachers. The researcher took observation notes during the in-class teaching exercises. The findings revealed that there were significant differences between the student teachers' pre and post-test scores. They understood science concepts signiﬁcantly better by the end of the course. It is concluded that combining different teaching methods enhances science concept understanding among student teachers.  In addition, misconceptions decreased after instruction.